Workplace sexual harassment is associated with poor mental well-being among employees at a large Swedish university - Frida Pilgaard; Per-Olof Östergren; Gisela Priebe; Anette Agardh (Global Health Action)
Background Sexual harassment (SH) is a persistent problem at workplaces around the world, including academia. Objective This study examines the association between SH and mental well-being among employees at Lund University (LU) in Sweden. Methods Data was obtained from a cross-sectional survey targeting all LU employees in 2019. SH exposure was measured using a ten-item scale capturing SH experiences and enabling the differentiation between soliciting and non-soliciting types of SH. Validated instruments were used to measure two aspects of mental well-being; mental health (GHQ-12) and vitality (SF-36 vitality scale). Association between SH exposure and outcome variables was investigated through multivariable logistic regression analysis adjusting for confounders. Modifying effects of gender, age, background and academic position, respectively, on the relation between SH and outcomes were studied. Results Workplace SH was associated with poor mental health (PMH) (OR 1.5 (95% CI 1.1–2.0)) and low vitality (LV) (OR 1.8 (95% CI 1.3–2.5)) among women and with LV (OR 2.0 (95% CI 1.1–3.9)) among men, after adjusting for confounders. Among women, experiences of non-soliciting and soliciting SH combined were associated with PMH and LV. Among men, experiences of non-soliciting SH behaviours exclusively were associated with LV. Indications of synergistic interaction affecting the association between SH and LV were found related to age, background and academic position, but not gender. Conclusions Workplace SH is a significant risk factor for poor mental well-being, primarily among female, but also among male university employees. These findings can inform local policies for prevention of SH.